UJI TOKSISITAS MINYAK ATSIRI DAUN TENGGULUN (Protium javanicum Burm. F.) DENGAN METODE BRINE SHRIMP LETHALITY TEST (BSLT) - Ni Luh Putu Putri Setianingsih; I Wayan Suirta; Ni Made Puspawati (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2013)
Toxicity of essential oils extracted from young and old leaves of Tenggulun (Protium javanicum, Burm) towards Artemia salina leach larvae has been evaluated using Brine Shrimp Lethality Test and their chemical compositions have been analyzed using Gas Chromatography-Mass Spectrometry (GC-MS). The essential oils were obtained by extracting fresh young and old leaves of Tenggulun using steam distillation method. Steam distillation of young leaves produced oils with 0.06% yield while old leaves yielded 0.07 % oils. The toxicity test results found thatthe essential oils obtained from old leaves were more toxic with LC50 of 15.85 compared to the essential oils of young leaves whose LC50 was 25.12 ppm. GC-MS data revealed that the essential oils of young leaves contained 11 compounds which were : ?-pinene (0.75 %), ?-pinene (0.54 %), delta-3-carene (0.38 %), octatriene (1.35%), trans-?-ocimene (77.63 %), ?-elemene (1.23 %), trans-caryophyllene (12.62 %), ?-humulene (1.18 %), germacrene (3.25 %), ethanone (0.65 %) and isospathulenol (0.42 %) while the essential oils of old leaves composed of 21 compounds whichwere : ?-pinene (0.71 %), ?-pinene (0.44 %), ?-myrcene (0.15 %), cis-ocimene (2.06 %), trans-?-ocimene (52.79 %), trans-caryophyllene (30.02 %), ?-humulene (2.80 %), germacrene (0.28 %), germacrene (4.64 %), ?-farnesene (0.85 %), ?-elemene (0.16 %), tridecatrienenitrile (0.19 %), ethanone (0.49 %), caryophyllene oxide (0.83 %), nerolidol (0.12 %), spathulenol (1.25 %), isospathulenol (1.18 %), kauran (0.30 %), isospathulenol (0.16 %), spathulenol (0.34 %) and ?-farnesene (0.23 %).